Characteristics of Physiological 18F-Fluoro-2-Deoxy-D-Glucose Uptake and Comparison Between Cats and Dogs With Positron Emission Tomography - Chae, Yeon; Yun, Taesik; Koo, Yoonhoi; Lee, Dohee; Kim, Hakhyun; Yang, Mhan-Pyo; Kang, Byeong-Teck (Frontiers in Veterinary Science, 2021)
This study aimed to identify the physiological 18F-fluoro-2-deoxy-D-glucose (FDG) uptake in cats using positron emission tomography/computed tomography (PET/CT) and determine its characteristics by comparing physiological differences with dogs. Seven healthy cats and six healthy beagle dogs were examined using FDG-PET/CT. Regions of interest (ROIs) were manually drawn over 41 detailed structures of 5 gross structures (brain, head and neck, musculoskeleton, thorax, and abdomen). The mean and maximum standard uptake values (SUVmean and SUVmax) were calculated for each ROI. Physiological variation was classified as having increased radiopharmaceutical activity with no evidence of abnormal clinical or radiological findings. The brain had the highest SUV, which was observed in the cerebellum of both cats (SUVmean: 4.90 ± 1.04, SUVmax: 6.04 ± 1.24) and dogs (SUVmean: 3.15 ± 0.57, SUVmax: 3.90 ± 0.74). Cats had a significantly higher intracranial uptake than dogs did (P<0.01). In the digestive system, the SUVs of the duodenum and jejunum were significantly higher in dogs than in cats (P<0.05). FDG uptake of the submandibular tip, tonsils, neck of the gallbladder, and caudal colliculus were physiologically increased in cats. This study demonstrates physiological FDG uptake in normal tissues, and the differences between cats and dogs were interpreted based on species-specificity. This information contributes to improving the accurate diagnosis of cancer in cats and will aid in understanding glucose metabolism in both cats and dogs.